Overview of solar technologies for electricity, heating and cooling production. (July 2018) - Settino, Jessica; Sant, Tonio; Micallef, Christopher; Farrugia, Mario; Spiteri Staines, Cyril; Licari, John; Micallef, Alexander
Abstract: The efficient use of local renewable energy sources is a key factor to reach the EU's targets on climate change and renewable energy. In this review, the available technologies to convert solar energy into electrical and thermal energy are investigated. Photovoltaic panels, thermal collectors, heat pumps, solar cooling and energy storage systems are analyzed with a particular attention to their market availability for small-scale applications. Different ways to provide heating, cooling and sanitary hot water from solar source are analyzed and compared from an efficiency, economic and environmental perspective.